Changes in the Plasma Sex Hormone Profile in Males with Severe Concomitant Injury - K. N Yezhova; A. V. Volkov; D. A. Ostapchenko; V. V. Moroz (Общая реаниматология)
Objective: to perform a complex study of typical plasma sex hormone changes and their functional significance in males with severe concomitant injury (SCI). Subjects and methods. Fifty-nine males aged 18—49 years who had SCI were enrolled in the study. The admission severity was an APACHE II score of 18.6±2.4. According to the outcome of the disease, all the patients were divided into 2 groups: A) survivors; B) deceased persons. A control comprised 12 healthy male donors aged 19-36 years, in whom the levels of 8 sex steroids were measured. The standard procedures were used to comparatively analyze the concentrations of pituitary reproductive hormones and aldosterone. Hormonal concentrations were studied over time on posttraumatic days 1, 3, 5, 7, 10, and 15. The plasma hormone profile was examined by test kits (BSL, USA) on a Stat Fax 2100 device (Awareness Technology Inc., USA) for enzyme immunoassay. Prolactin, luteinizing hormone (LH), follicle-stimulating hormone (FSH), progesterone (P), 17-hydroxyprogesterone (17-OH-P), dehydroepiandrosterone sulfate (DHEA-S), androstendione (A), testosterone (T), dihydrotestosterone (DHT), estrone (E1), estradiol (E2), and aldosterone were determined. Results. The complex study of phasic changes in the profile of 11 plasma sex hormones was first conducted in males in the posttraumatic period. Moreover, the typical plasma hormonal changes were elevated prolactin levels and their phasic variations, normal LH and FSH levels with a tendency for further phasic LH changes and FSH reduction. After the injury, the plasma concentration of P was increased and that of 17-OH-P was decreased. The levels of A and DHEA-S varied in the normal range with a tendency for DHEA-S to be lower during the process. In the posttraumatic period, the plasma content of T and DHT was substantially reduced and that of E1 and E2 was increased. The deceased patients generally showed higher levels of A, DHEA-S, and estrogens as a reflection of dysregulatory pathology and complications. The changes revealed in hormonal levels are of significance in understanding the pathogenesis of SCT and its sequels. This may serve as a basis for the development of new therapy methods using sex hormones as adaptogens in the postresuscitative period. Key words: severe concomitant injury, sex hormones, prolactin, luteinizing hormone, follicle-stimulating hormone, progesterone, 17-hydroxyprogesterone, androgens, estrogens.